3e Methodology for Tuff Stones As Wall Coating Material - Sua, Lutfu S.; Yilmaz, Unal; Balo, Figen (Elsevier B.V., 2019)
Tuff stones originating from Koÿke stone or Isparta volcanic stones have a soft feature (due to high porosity) which can retain natural moisture content when first excavated and their surfaces can be formed. These stones, which have been used in wall claddings since ancient times, have become more and more stable and gradually survive for thousands of years. They also have been used in the covering of the walls of mosques and churches in Isparta Province; have survived for 2000 years and without being affected by atmospheric conditions. Physical-mechanical properties of Isparta region tuffs do not comply with normal marble and natural stone standards because some of the time-dependent properties of these stones change positively. In addition, in the heat insulation tests where the village stone is kept, it has been reported that these stones are in the standards that can contribute to the thermal insulation. In these studies, it is stated that buildings have a chemical and physical structure that can contribute to reducing the cooling and heating costs. In the first step of this study, general properties and usage areas such as physical, chemical, mechanical and thermal properties of Koÿke stone were investigated. Then, in order to determine its contribution to the energy, ecology and economy (3E), analysis of the effect of the use of Koÿke stone together with the different wall materials which are frequently applied in today's buildings as the outer wall cladding material in the climate conditions of Isparta city is conducted. For the analysis, ANSYS package program was used. In this study, as an alternative to fossil based materials, the benefits of using natural materials in people's habitats as well as in all areas of industry are evaluated in terms of both health and energy-ecology-economics. © 2019 The Authors. Published by Elsevier B.V.
3rd World Conference on Technology, Innovation and Entrepreneurship, WOCTINE 2019 -- 21 June 2019 through 23 June 2019 -- Istanbul -- 141488
Keywords: Energy; Natural stone; Sustainability; Tuff stone; Wall coating material